Co-targeting intracellular pH and essential amino acid uptake cooperates to induce cell death of T-ALL/LL cells. Issue 2 (1st February 2018) - Imbert, Véronique; Nebout, Marielle; Mary, Didier; Endou, Hitoshi; Wempe, Michael F.; Supuran, Claudiu T.; Winum, Jean-Yves; Peyron, Jean-François
Abstract: Cancer cells reprogram their metabolism to optimize their growth and proliferation in the host microenvironment. For this purpose, they enhance the uptake of extracellular nutrients and deal with the metabolic waste products through the overexpression of numerous membrane proteins including amino-acid transporters (LAT1) and acid-base regulating enzymes, such as carbonic anhydrases (CAs). Here we describe the anti-tumoral effects of a new class of CAXII inhibitors, the glycosyl coumarins on T-ALL/LL cells. These effects appeared to be mediated through inhibition of mTOR/Akt pathway and c-myc downregulation. Interestingly, we show that the combined targeting of amino acid fluxes and pH regulators provides a promising therapeutic strategy in the future of T-ALL/LL management.